Lista patron de los mamiferos de Nicaragua / Martínez Sánchez, Juan C. Morales Velásquez, Salvadora Castañeda Mendoza, Edgar A. - Martínez Sánchez, Juan C. Morales Velásquez, Salvadora Castañeda Mendoza, Edgar A. (Nicaragua, 2000)
Lista de patrón de los a mamíferos de Nicaragua, especies esperadas en N Nicaragua
Col. Agro
Keywords: 1. ZOOTECNIA 2. MAMIFEROS-NICARAGUA